Body Composition Parameters and Relationship with the Maximal Aerobic Power in Recreational Cyclists [Parámetros de Composición Corporal y Su Relación Con la Potencia Aeróbica Máxima en Ciclistas Recreacionales] - Herrera-Valenzuela, T (Grupo Aula Medica S.A., 2015)
Objective: the aim of this study is to relate body composition parameters on performance in recreational cyclists using fat mass (MG), total muscle mass (MM) and the appendix of the lower extremity (MMEI) with maximal aerobic power (PAM). Methods: 11 male cyclists (27.7 ± 4.5 years; 72.4 ± 12.4 kg; 173.2 ± 6.7 cm.) were recruited. The anthropometric measurements were performed according to the protocols of the International Society for the Advancement of Kineanthropometry (ISAK) and testing of PAM were held following a ramp protocol, which began with an initial load of 150 W and then increments 30 W at 1-minute intervals until exhaustion. Results: there is dependence between variables and the VO2max MG that correlate negatively and significantly (p < 0.05). MM respect to variables and the VO2max significantly negatively correlated (p < 0.05). In correlation with the PAM, MMEI it can be seen a positive and significant correlation (p < 0.01) indicating that individuals who have greater muscle component in the lower limbs (EEII) are able to generate more power. Conclusions: we conclude that the results obtained, both the MG and the MM are not a good reference as performance parameters regarding the VAM. The MMEI was the only parameter that showed a positive relationship as a marker of performance in recreational cyclists. © 2015, Grupo Aula Medica S.A. All rights reserved.